Efeito do processo de descafeinação de café arábica em meio aquoso auxiliado por ultrassom sobre a composição química e o perfil sensorial - Henao, Carolina Pérez [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Decaffeinated coffee market has achieved significance and relevance, nevertheless, methods of caffeine extraction may eventually result in loss of chemical compounds, like chlorogenic acids, carbohydrates, trigonelline and proteins, which are important for taste formation, fragrance and aroma and which are determinant for the coffee beverage quality, as well as, loss of antioxidants compounds in coffee, which may be associated to healthy benefits. The purpose of this study was to evaluate the impact of an alternative decaffeination process, using water as solvent, and assisted with high intensity ultrasound applied to coffee beans Arabica variety, on the physical characteristics (dimensions, particle size distribution, sphericity and density) and on the contents of caffeine, chlorogenic acids, sugars and total lipids, as well as, to evaluate the sensory profile of decaffeinated coffee using the Optimized Descriptive Profile method. Results were compared to the decaffeinated coffee obtained from both organic solvent (dichloromethane) extraction and water extraction without using ultrasound. In order to achieve such goals, judges were selected based on their sensory analysis skills and then trained to improve repeatability and consensus, resulting in a trained group with a very satisfactory performance for coffee evaluation. For raw material and decaffeinated coffee, a HPLC-MS protocol was developed and tested aiming to quantify caffeine and chlorogenic acids; in addition, a mass spectrometry protocol was developed in order to identify main isomers of chlorogenic acids (3-CQA, 4-CQA and 5-CQA). The results showed that water ultrasound-assisted decaffeinated coffee had no significant losses for the contents of sugars, lipids, 3-CQA and 4-CQA, and the physical dimensions of the coffee beans (width and thickness) were not affected. The sensory profile did not show differences in its descriptors relative to the raw material coffee, excepted for...

O mercado do café descafeinado encontra-se em expansão, embora, a extração da cafeína possa, eventualmente, resultar em perdas de compostos químicos tais como ácidos clorogênicos, açúcares, trigonelína, lipídios e proteínas, compostos importantes para a formação do sabor, aroma e fragrância que determinam a qualidade final da bebida de café, assim como também podem-se perder compostos associados com os efeitos saudáveis como os antioxidantes presentes no café. A pesquisa teve como objetivos avaliar o impacto do processo alternativo de descafeinação usando água como solvente auxiliado por ultrassom de alta intensidade nas características físicas (dimensões, granulometria, esfericidade e densidade) e nos teores de cafeína, ácidos clorogênicos (ACG), açúcares e lipídios totais em grãos de café da variedade arábica, e, adicionalmente, avaliar o perfil sensorial da bebida do café descafeinado pelo método denominado Perfil Descritivo Otimizado. Os resultados foram comparados com os obtidos para café descafeinado com solvente orgânico (diclorometano) e para o café descafeinado com água em ausência de ultrassom. Para atingir tais objetivos foi realizada a seleção de julgadores com habilidades para análise sensorial, os quais foram treinados para a avaliação de café e foi avaliada a repetibilidade e consenso, sendo satisfatórios seus resultados para serem utilizados como julgadores na avaliação da bebida dos diferentes cafés. Foram desenvolvidas e testadas metodologias para analisar o café matéria prima e café descafeinado, visando à quantificação da cafeína e ácidos clorogênicos por protocolo em HPLC-MS, e, por espectrometria de massas (MS) foi possível identificar os isômeros majoritários dos ACG como 3-CQA, 4-CQA e 5-CQA. Os resultados mostraram que o café descafeinado com água e auxílio de ultrassom apresentou perdas não significativas nos teores...
Keywords: Tecnologia de alimentos; Café; Ultrasson